2000
DOI: 10.2174/1381612003399725
|View full text |Cite
|
Sign up to set email alerts
|

Drugs with Estrogen-like Potency and Brain Activity Potential Therapeutic Application for the CNS

Abstract: Numerous reports, ranging from molecular investigations to clinical studies, demonstrate the potency of estrogens to modulate brain function and their implications in schizophrenia and depression. Alterations of dopaminergic, cholinergic, GABAergic, glutamatergic and serotonergic neurotransmission through estrogen-mediated mechanisms have been consistently established. Moreover, studies using in vivo and in vitro models as well as epidemiological data suggest that estrogens provide neuroprotection of central n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 277 publications
(374 reference statements)
1
73
0
4
Order By: Relevance
“…In general, the biological actions of estrogens can be mediated through a rapid nongenomic and a delayed genomic mechanism (Cyr et al, 2000;McEwen, 1991McEwen, , 1999Wehling, 1997;Wise et al, 2001). The first mechanism is mediated by membrane receptors and second messengers (Cyr et al, 2000;McEwen et al, 2001;Nadal et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, the biological actions of estrogens can be mediated through a rapid nongenomic and a delayed genomic mechanism (Cyr et al, 2000;McEwen, 1991McEwen, , 1999Wehling, 1997;Wise et al, 2001). The first mechanism is mediated by membrane receptors and second messengers (Cyr et al, 2000;McEwen et al, 2001;Nadal et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The first mechanism is mediated by membrane receptors and second messengers (Cyr et al, 2000;McEwen et al, 2001;Nadal et al, 2000). The other mechanism involves the interaction with intracellular receptors that implies the activation of transcription factors (McEwen, 1991;McEwen et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the neuroprotective and neurotrophic effects of 17b-estradiol it is not surprising that its use as an adjunct treatment in a number of disorders has been investigated. Results for a limited number of clinical studies have indicated a potential beneficial role of estrogens in disorders such as schizophrenia (Cyr et al, 2000;Kulkarni et al, 2008;Hughes et al, 2009;Kulkarni, 2009;Sanchez et al, 2010b). However, it must be noted that longterm treatments of women aged 65 years with conjugated equine estradiol and medroxyprogesterone showed no beneficial effect of this treatment in protection against cognitive decline.…”
Section: E Estrogenic Regulation Of Neural Circuitry and Diseasementioning
confidence: 99%
“…Moreover the non-genomic effect of steroids could be attributed to their binding with the sex-hormon-binding globulin (SHBG) receptor, that is a G-protein-coupled receptor (GPCR), located at the membrane and has been functionally identified in a number of tissues such as prostate, testis, liver, and breast [78,79]. Finally, the rapid steroid action could potentially be induced in the absence of a receptor, by influencing membrane fluidity [80,81].…”
Section: Estrogen Receptor Transcriptionmentioning
confidence: 99%